PHOTAR: Media Based on Articulate Storyline to Improve Student Interest in Learning - Sri Lestari Handayani; Putri Dwi Destiasari (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2026)
Students’ learning interest in elementary schools is an essential aspect of education; however, low levels of interest often cause students to become passive during the learning process. This study aims to identify the factors contributing to low learning interest and to enhance it through the development of Photar media based on Articulate Storyline. The method used is Research and Development (R&D) with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. In the analysis stage, a needs analysis was conducted through questionnaires and interviews involving 25 fourth-grade students at SDN Mampang Prapatan 01 Pagi to measure learning interest. The results showed that 94% of students needed the use of learning media, which was influenced by the dominance of lecture-based teaching methods. The research instruments included a pre-learning interest questionnaire, expert validation sheets, and student response questionnaires. The indicators of learning interest measured were attention, interest, engagement, and enjoyment. The development stage produced media validated by media experts (87%), material experts (88%), and language experts (86%). In the implementation stage, 93% of students expressed satisfaction with the learning media used. This study contributes to the advancement of interactive Photar learning media aimed at enhancing students’ interest in learning. The implementation of Photar media at SDN Mampang Prapatan 01 Pagi serves as an innovative approach in the instructional process, as it effectively fosters students’ learning interest by providing media that corresponds to their needs and preferences.